Legitimasi Resolusi Dewan Keamanan PBB dalam Konflik di Darfur Sudan - Darnela, Lindra (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Massive demonstrations  in  several  Arab  countries  lead to a civil war among the citizens. This is of special concern to the United  Nations  as  the  global  nature  of  international organizations  to  participate  in  the  intervention  of  the  conflict accompanied  by making  resolutions.  These cases are  suing  back the  legitimacy  of  international  law,  especially  international organizations  like  the  UN.  In  this  study  describes  about  the legitimacy  of  the  UN  Security  Council  resolutions,  and  thenapply  it  to  analyze  the  conflict  in  Darfur.  The  UN  is  an international  organization  which  is  the  subject  of  public international  law,  so  that  the  resulting  public  policy  becomes legally  binding  for  member  states  based  on  the  collective legitimation.  In  the  application  of  collective  legitimation  is  in practice  often does not  correspond to  the value of  morality  and even  a lot of  opposition  as in  the case of  the conflict in  Darfur whose governments  openly  reject the  contents of  the resolution issued by the United Nations.